Parental origin of mutation and the risk of breast cancer in a prospective study of women with a BRCA1 or BRCA2 mutation. (7th November 2012) - Senst, N; Llacuachaqui, M; Lubinski, J; Lynch, H; Armel, S; Neuhausen, S; Ghadirian, P; Sun, P; Narod, SA; ,
<x xml:space="preserve">Abstract</x> The objective is to estimate the risk of breast cancer in women who carry a deleterious BRCA1 or BRCA2 mutation, according to parental origin of mutation. We conducted a cohort study of women with a BRCA1 mutation (n = 1523) or BRCA2 mutation (n = 369) who had not been diagnosed with breast or ovarian cancer. For each woman, the pedigree was reviewed and the origin of the mutation was assigned as probable paternal or maternal. The hazard ratio (HR) for developing breast cancer in the follow‐up period was estimated for women with a paternal mutation compared to a maternal mutation. The risk of breast cancer was modestly higher in women with a paternal BRCA1 mutation compared to women with a maternal BRCA1 mutation (HR = 1.46; 95% CI = 0.99–2.16) but the difference was not significant (p = 0.06). The parental mutation origin did not affect the risk in women with a BRCA2 mutation. Our results are consistent with the hypothesis that there is an increased risk of breast cancer among women with a paternally inherited BRCA1 mutation compared to a maternally inherited mutation. However, the data are not sufficiently compelling to justify different screening recommendations for the two subgroups.